Strategi Meningkatkan Kepatuhan Wajib Pajak Badan dan Orang Pribadi - Windy Noviana (Universitas Pendidikan Nasional, 2018)
ABSTRACTThis research studies about taxpayers compliance level both corporate and institutional taxpayers with an annual gross turnover below IDR 4.8 billion following the Government Regulation No 46 Year 2013 with 1% tax rate on gross turnover in Gianyar Small Taxpayers Office, and efforts which must be undertook by Gianyar Small Taxpayers Office to elevate tax compliance and to obtain potential taxpayers to register for tax identification number (NPWP).Population used in this research are institutional and individual taxpayers registered in Gianyar Small Taxpayers Office and tax officers including Account Representatives and Chief of Monitoring and Consulting Section. Data collecting perfomed by profound interview method. Participants determined by purposive sampling technique and the validity of analysis result verification by data triangulation. The results of this research show that taxpayers violation is contributed by five factors, which are, Taxpayers awareness, tax officers service quality, perception on tax administration effectivity, tax simplicity, and tax penalties. Efforts executed by Gianyar Small Taxpayers Office in escalating taxpayers compliance include decreasing tax rate, prevalent socialization in all over the place regarding methods of tax reporting and payment, performing excellent service, imposing administration charge equitably for all taxpayers, and alternate solutions availability for technology illiterate taxpayers.Efforts should be made for obtaining new Taxpayers are sweeping to strategic business location, data searching through internet or third parties and socialization to encompass unregistered Taxpayers. Policy and theoretical implication in this study have given empirical evidence over factors causing taxpayers incompliance, efforts needed to be done to elevate compliance and to obtain new unregistered Taxpayers so that it can give contribution to DGT to increase taxpayers compliance in completing their tax obligation. For future research, it is expected to use measurement other than Planned of Behavior theory used in this study, for instance, atribution theory, and the others so that comparation can be done for more extensive and accurate results.